2020
DOI: 10.3390/ijms21155553
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Colony-Stimulating Factor 1 Receptor by PLX3397 Prevents Amyloid Beta Pathology and Rescues Dopaminergic Signaling in Aging 5xFAD Mice

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disease. In this study, to investigate the effect of microglial elimination on AD progression, we administered PLX3397, a selective colony-stimulating factor 1 receptor inhibitor, to the mouse model of AD (5xFAD mice). Amyloid-beta (Aβ) deposition and amyloid precursor protein (APP), carboxyl-terminal fragment β, ionized calcium-binding adaptor molecule 1, synaptophysin, and postsynaptic density (PSD)-95 levels were evaluated in the cortex and hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Microglia may play bidirectional roles for Aβ clearance via phagocytosis, endolysosomal clearance, and seeding of Aβ aggregates depending on the age of animals and the stage of Aβ accumulation in the brain. The general consensus of previous research regarding the effect of microglia depletion on amyloid deposition is that it is largely ineffectual aside from those utilizing the 5xFAD mouse model, which report dramatic improvements of Aβ pathology following microglia depletion [ 20 , 47 49 ]. Here we found that microglia depletion causes a sizeable increase in compact, but not diffuse amyloid deposition ( Supplemental Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microglia may play bidirectional roles for Aβ clearance via phagocytosis, endolysosomal clearance, and seeding of Aβ aggregates depending on the age of animals and the stage of Aβ accumulation in the brain. The general consensus of previous research regarding the effect of microglia depletion on amyloid deposition is that it is largely ineffectual aside from those utilizing the 5xFAD mouse model, which report dramatic improvements of Aβ pathology following microglia depletion [ 20 , 47 49 ]. Here we found that microglia depletion causes a sizeable increase in compact, but not diffuse amyloid deposition ( Supplemental Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, microglial reduction via CSF1R inhibition was found to rescue several cognitive deficits in Dp16 mice (Pinto et al, 2020 ). In AD mouse models, microglial depletion prior to amyloid deposition was shown to be critical for therapeutic efficacy (Sosna et al, 2018 ; Spangenberg et al, 2019 ; Son et al, 2020 ). Likewise, in mouse models of primary tauopathy, characterized by inclusions of the protein tau in neural cells (Kovacs, 2015 ), CSF1R inhibitors reduced pathological tau aggregation and subsequent neurodegeneration (Mancuso et al, 2019 ; Shi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current clinical use of CSF1R inhibitors further confirms that short-term administration of CSF1R inhibitors can effectively eliminate human microglia (Butowski et al, 2016). Therefore, short-term elimination of microglia and cell proliferation may be a clinically feasible and novel method to solve neuroinflammatory events and promote brain recovery in brains affected by microglial dysfunction (Rice et al, 2017;Son et al, 2020). However, Since the recently obtained information on the different roles of microglia mainly comes from studies in mouse disease models, it is necessary for us to develop new disease models, including human induced pluripotent stem cells (iPSCs; Muffat et al, 2016;Bohlen et al, 2017;Gosselin et al, 2017), to fully understand which findings can be translated from mice to humans.…”
Section: Discussionmentioning
confidence: 83%